2009
DOI: 10.1111/j.1095-8312.2009.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-limited fecundity and polyandry-induced mortality in female nematodes Caenorhabditis remanei

Abstract: In many sexually reproducing species, females are sperm limited and actively mate more than once which can lead to sperm competition between males. However, the costs and benefits of multiple matings may differ for males and females leading to different optimal mating frequencies and consequent sexual conflict. Under these circumstances, male traits that reduce females' re-mating rates are likely to evolve. However, the same traits can also reduce, directly or indirectly, female survival and/or manipulate fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…9 females cannot take full advantage of abundant sperm. This may be a general feature of the species, for example as a consequence of female spermatheca size, barriers to remating, male effects on female fecundity (Diaz et al 2010), or as a consequence of unintended inbreeding in our laboratory stocks. Additionally, the reduction of C. briggsae hermaphrodite brood size by C. sp.…”
Section: Reproductive Isolation In Caenorhabditismentioning
confidence: 99%
“…9 females cannot take full advantage of abundant sperm. This may be a general feature of the species, for example as a consequence of female spermatheca size, barriers to remating, male effects on female fecundity (Diaz et al 2010), or as a consequence of unintended inbreeding in our laboratory stocks. Additionally, the reduction of C. briggsae hermaphrodite brood size by C. sp.…”
Section: Reproductive Isolation In Caenorhabditismentioning
confidence: 99%
“…Caenorhabditis remanei female fitness decreases with the number of mating partners and therefore represents a perfect fit for our experiment [32]. We intensified sexual conflict to females above the laboratory baseline (1 : 1 sex ratio) for 20 generations by imposing a 1 : 5 (polyandry, PA) sex ratio and relaxed it using a 5 : 1 (polygyny, PG) sex ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the receipt of sperm can represent a material benefit, if female reproductive success is limited by the number of sperm that is available to fertilize all the eggs (e.g., Pitnick 1993; Levitan and Petersen 1995;Fjerdingstad and Boomsma 1998;Diaz et al 2010). Several empirical studies across a wide range of taxa have demonstrated that repeated matings are advantageous to females (e.g., Wagner et al 2001;Fedorka and Mousseau 2002;Schwartz and Peterson 2006;Klemme et al 2007), which suggests that direct benefits may promote the evolution of multiple mating.…”
Section: Introductionmentioning
confidence: 99%